Great Fish River: promoting sound fishing practices - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
Margot Collett explains how researchers in South Africa´s Great Fish River project are using acoustic telemetry to help in the design of conservation strategies for the estuary´s fisheries.